Morphometric Analysis of Superior Articular Surface of Tibia in Dry Cadaveric Bones - Pandit, Ruku; Sharma, Nitasha (Journal of College of Medical Sciences-Nepal, 2019)
Background: Total knee arthroplasty is the most cost effective and rapidly evolving technique. The success of procedure relies on appropriate sizing of tibial component, for which elaborate information of various dimensions of upper surface of tibia is mandatory. Hence, this study is aiming to generate baseline data on antero-posterior and transverse measurements of medial and lateral condyles and intercondylar area of upper surface of tibia. Methods: The study was conducted in 42 dry human cadaveric tibia with unidentified age and sex, in the Department of Anatomy, College of Medical Sciences and Teaching Hospital, Chitwan. The antero-posterior and transverse measurements of medial and lateral condyles and intercondylar area of tibia were recorded in millimeter (mm) with digital Vernier calipers. The data was analysed using SPSS version 16.0. Results: The antero-posterior and transverse measurements of medial condyle of tibia were 43.00±5.95 mm and 25.21±8.08 mm respectively on the right side and 45.33±5.36 mm and 27.43±8.57 mm respectively on the left side and that of lateral condyle were 37.94±5.64 mm and 25.21±8.71 mm respectively on the right side and 41.03±3.65 mm and 27.06±8.83 mm respectively on the left side. The antero-posterior and transverse measurements of intercondylar area of tibia were 47.49±6.31 mm and 15.71±3.93 mm respectively on the right side and 49.24±6.91 mm and 15.02±3.88 mm respectively on the left side. The variation in the measurements between right and left tibia showed significant difference only for antero-posterior measurement of lateral condyle (p<0.05). Conclusions: The study generates baseline data regarding various anthropometric measurements of upper surface of tibia, which will assist the orthopedic surgeon to create a resected bony surface identical to the tibial component of an implant in unilateral and total knee arthroplasty. Keywords: measurement; morphometric; superior articular surface; tibial condyles.